THE EFFECTIVE OF USING SQR3 METHOD IN STUDENT’S READING COMPREHENSION - Hijril Ismail (Linguistics and ELT Journal, 2015)
This study focused on the analysis of the effectiveness of applying the SQR3 method in student’s reading comprehension in the second year students of MA At-tahzib Gunung Sari in academic year 2015/2016. It was aimed at answering the research question ‘’Is SQR3 method effective in teaching student’s reading comprehension?’’ The population of this study was the grade XI students of MA At-tahzib Gunung Sari. The sample of this study was the students of class XI IPA 1 (experimental group) and XI IPA 2 (control group) with a total sample of 52 students from both classes. The writer conducted the research starting from giving pre-test, treatment, and post-test. In the process of treatment, both groups were treated differently. The experimental group was treated using the SQR3 method, while the control group was not treated by using the SQR3 method. Based on the finding, it was suggested that the SQR3 method can be used by the English teacher as a method in teaching, especially in teaching reading. The result of the test showed that the mean score of the experimental group was 25.07 which was higher than the mean score of the control group (9.65). It was also supported by the t-test (6.85) which was higher than t-table at the confidence level of .05 (95%). Therefore, the alternate Hypothesis (Ha) which stated” SQR3 method is effective in teaching student’s reading comprehension” is accepted. It means that the SQR3 method is effective in teaching student’s ability in reading comprehension for the second year students of Ma-Attahzib Gunung Sari in academic year 2015/2016.